Al-Ārā’ al-Balāghiyyah li Sheikh al-Azhar Muḥammad Sayyid Ṭanṭāwī fī Tafsīr al-Wasīṭ [Arabic Rhetorical Opinions of Sheikh al-Azhar Muhammad Sayyid Tantawi in the Tafsir al-Wasit] - Mirwan Akhmad Taufiq; Elseed, Mohammad Elnour Gasm (OKARA: Jurnal Bahasa dan Sastra, 2023)
A linguistic interpretation appeared at the hands of the Sheikh al-Azhar, Muhammad Sayed Tantawi, whose field was in tafsir. He wrote a tafsir book of the Holy Qur'an in thirty volumes until he became famous as an interpreter, modernizer, and Islamic thinker. He formulated his interpretation with balāghah's (Arabic Rhetoric) explanation in linguistic studies. The problem was whether Sheikh al-Azhar specialized in linguistic studies. This study aims to find his scientific personality and creativity in the balāghah explanation. The researchers used inductive and analytical approaches in three sections (juz) of Tafsīr al-Wasīṭ: the first, second, and third. The finding is that Sheikh al-Azhar was a prominent figure in the balāghah aspect, as he created a single opinion when explaining the rhetorical verses of the Qur'an. In his explanation, he may transfer from the books of the former interpreters. However, he was not only satisfied with conveying their opinions but also showed the existence of scientific discussion among the interpreters, adding a new opinion, preferring an opinion, or confirming a correct opinion by relying on Arabic grammar, tafsir, and hadith. This work indicated the existence of multidisciplinary studies in linguistics and Islamic studies.